1987
DOI: 10.1182/blood.v70.4.932.bloodjournal704932
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of a novel pre-B cell component in plasma cell myeloma: immunochemical, immunophenotypic, genotypic, cytologic, cell culture, and kinetic features

Abstract: A novel pre-B cell component in direct and cultured myeloma bone marrow material has been delineated by using immunochemistry and flow cytometry techniques. Our phenotypic studies suggest a novel hybrid expression of pre-B and plasma cell antigens with coexpression of cytoplasmic mu, common acute lymphoblastic leukemia antigen, terminal deoxynucleotidyl transferase, and plasma cell antigens (PCA-1 and PC- 1). This suggests that myeloma pre-B-like cells are aberrant malignant cells and not normal pre-B lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
5

Year Published

1989
1989
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 34 publications
0
17
1
5
Order By: Relevance
“…The second supposition cannot be ruled out but gives no explanation for the existence of a proliferating B lymphocyte population, which has been observed carrying the same idiotype and the same gene rearrangement as the plasmocytic cells and which have been recognized as malignant progenitor cells by various investigators (5, (,,8,22,31,40-42,4(,,48,53). There are studies showing that, in MM, a population of pre-B cells is the target for an oncogenic event, which does not block differentiation to plasmocytic cells ( 12,17,22,23,27,32,37,43,45,47). The third possiblity is equivocal but may be correct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second supposition cannot be ruled out but gives no explanation for the existence of a proliferating B lymphocyte population, which has been observed carrying the same idiotype and the same gene rearrangement as the plasmocytic cells and which have been recognized as malignant progenitor cells by various investigators (5, (,,8,22,31,40-42,4(,,48,53). There are studies showing that, in MM, a population of pre-B cells is the target for an oncogenic event, which does not block differentiation to plasmocytic cells ( 12,17,22,23,27,32,37,43,45,47). The third possiblity is equivocal but may be correct.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of cellular DNA content by flow cytometry (FCM) has revealed the existence of an aneuploid plasma cell population in 65-75% of the MM bone marrow samples with a median DNA index of 15% above normal (2,3, 9,11,34,35,53). Most aneuploid tumor cells show a cell marker that is consistent with differentiated B cells, but subpopulations of tumor cells have been observed that express pre-B, early-B, or T lymphocytic, and even myelomonocytic or erythroid, features (16,17,22,23). Differentiation and lineage infedilities of plasmocytic cells in MM suggest that the malignant transformation involves a more pluripotent lymphoplasmacytoid precursor cell with a flexible pattern of gene expression.…”
mentioning
confidence: 99%
“…Moreover, recent reports document the presence of pre-B and B-cell antigens, and even of non-B cell (i.e. myelomonocytic) antigens on myeloma cells, suggesting that an early marrow progenitor cell may be part of the myeloma clone (37)(38)(39)(40)(41)(42)(43). Nonetheless, the phenotype of the "clonogenic" cell remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Several antigens have been described to date on the surface of normal and neoplastic plasma cells and are candidates for use in depleting these cells from autologous marrow prior to BMT for myeloma (29,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). We have utilized anti-PCA-1, a MoAb directed to a 26-kilodalton protein on the surface of myeloma cells which is of the IgG2a isotype and therefore capable of complementmediated lysis of antigen-bearing tumor cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This approach requires the tumor cells to be CD34-. In multiple myeloma the malignant transformation supposedly occurs in a highly proliferative pre-B cell [7], and others even postulate an earlier malignant pluripotent progenitor cell [8]. It has been shown that circulating lymphocytes bearing the early B cell marker CDlO can differentiate into myeloma cells [9].…”
Section: Introductionmentioning
confidence: 99%